1999
DOI: 10.1136/oem.56.6.403
|View full text |Cite
|
Sign up to set email alerts
|

Follow up investigation of workers in synthetic fibre plants with humidifier disease and work related asthma.

Abstract: Objective-To investigate the clinical and sociomedical outcome in patients with various clinical manifestations of humidifier disease and work related asthma after removal from further exposure. Methods-Follow up investigation (range 1-13 years) of respiratory symptoms, spirometry, airway responsiveness, sickness absence, and working situation in patients with (I) humidifier fever (n=12), (II) obstructive type of humidifier lung (n=8), (III) restrictive type of humidifier lung (n=4), and (IV) work related asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Twenty-four studies were included in the analysis . Seventeen studies were excluded due to insufficient data (31)(32)(33)(34)(35)(36)(37)(38)(39)(40), ineligible outcome (41)(42)(43)(44) or study population (45)(46)(47). Eighteen eligible studies were found through manual search of the reference lists of the relevant reviews and the acquired original studies (48-65) and 3 publications through other searches (on capacity and work ability) during the whole project (66)(67)(68).…”
Section: Literature Searchmentioning
confidence: 99%
“…Twenty-four studies were included in the analysis . Seventeen studies were excluded due to insufficient data (31)(32)(33)(34)(35)(36)(37)(38)(39)(40), ineligible outcome (41)(42)(43)(44) or study population (45)(46)(47). Eighteen eligible studies were found through manual search of the reference lists of the relevant reviews and the acquired original studies (48-65) and 3 publications through other searches (on capacity and work ability) during the whole project (66)(67)(68).…”
Section: Literature Searchmentioning
confidence: 99%